Research for Assessment, not Deployment of Climate Engineering: The German Research Foundation's Priority Program SPP 1689 - Andreas Oschlies; Gernot Klepper (Earth's Future, 2017)
The historical developments are reviewed that have led from a bottom–up responsibility initiative of concerned scientists to the emergence of a nationwide interdisciplinary Priority Program on the assessment of Climate Engineering (CE) funded by the German Research Foundation (DFG). Given the perceived lack of comprehensive and comparative appraisals of different CE methods, the Priority Program was designed to encompass both solar radiation management (SRM) and carbon dioxide removal (CDR) ideas and to cover the atmospheric, terrestrial, and oceanic realm. First, key findings obtained by the ongoing Priority Program are summarized and reveal that, compared to earlier assessments such as the 2009 Royal Society report, more detailed investigations tend to indicate less efficiency, lower effectiveness, and often lower safety. Emerging research trends are discussed in the context of the recent Paris agreement to limit global warming to less than two degrees and the associated increasing reliance on negative emission technologies. Our results show then when deployed at scales large enough to have a significant impact on atmospheric CO2, even CDR methods such as afforestation—often perceived as “benign”—can have substantial side effects and may raise severe ethical, legal, and governance issues. We suppose that before being deployed at climatically relevant scales, any negative emission or CE method will require careful analysis of efficiency, effectiveness, and undesired side effects.
Keywords: 330; climate engineering; assessment; solar radiation management; negative emission technologies